Aspectos actuales de las complejidades de la enseñanza del inglés en Costa Rica - Sevilla Morales, Henry (2017)
Current complexities of English teaching in Costa Rica’s public secondary education are discussed. Using an autoethnographic research approach, critical incidents of an EFL teacher are examined in light of Complexity Theory. Findings suggest that classrooms are unpredictable sites of struggle where multiple rationalities coexist (and often conflict), which must be understood before random decisions are made. For applied linguistics, the study is relevant at three levels: it expands the bulk of literature on the subject, it calls for more attention to the complexities of EFL, and it opens an avenue for reflection and future research directions.